Evaluation of Phytochemical, Antioxidant and Antibacterial Activities of Selected Medicinal Plants - Shresta, Shrimita; Bhandari, Sudip; Aryal, Babita; Marasini, Bishnu P.; Khanal, Santosh; Poudel, Pramod; Rayamajhee, Binod; Adhikari, Bikash; Bhattarai, Bibek Raj; Parajuli, Niranjan (Nepal Journal of Biotechnology, 2021)
Medicinal plants are important reservoirs of bioactive compounds that need to be explored systematically. Because of their chemical diversity, natural products provide limitless possibilities for new drug discovery. This study aimed to investigate the biochemical properties of crude extracts from fifteen Nepalese medicinal plants. The total phenolic contents (TPC), total flavonoid contents (TFC), and antioxidant activity were evaluated through a colorimetric approach while the antibacterial activities were studied through the measurement of the zone of inhibition (ZoI) by agar well diffusion method along with minimum inhibitory concentrations (MIC) by broth dilution method. The methanolic extracts of Acacia catechu and Eupoterium adenophorum showed the highest TPC (55.21 ± 11.09 mg GAE/gm) and TFC (10.23 ± 1.07 mg QE/gm) among the studied plant extracts. Acacia catechu showed effective antioxidant properties with an IC50 value of 1.3 μg/mL, followed by extracts of Myrica esculenta, Syzygium cumini, and Mangifera indica. Morus australis exhibited antibacterial activity against Klebsiella pneumoniae (ZoI: 25mm, MIC: 0.012 mg/mL), Staphylococcus aureus ATCC 25923 (ZoI: 22 mm, MIC: 0.012 mg/mL), Pseudomonas aeruginosa (ZoI; 20 mm, MIC: 0.05 mg/mL), and methicillin-resistant Staphylococcus aureus (MRSA) (ZoI: 19 mm, MIC: 0.19 mg/mL). Morus australis extract showed a broad-spectrum antibacterial activity, followed by Eclipta prostrata, and Hypericum cordifolium. Future study is recommended to explore secondary metabolites of those medicinal plants to uncover further clinical efficacy.